Analysis of The Issuance of Land Ownership Certificates on Riparian Land (Case Study of Land Ownership Certificate Number 913 in Demaan Village, Jepara) - Qodar Istikomah (Semarang State University Undergraduate Law and Society Review, 2025)
Land holds a vital position in human life, serving as a place of residence, a source of livelihood, and a legal instrument for ownership. In spatial planning and land use management, certain zones are restricted in their utilization,one of which is the riparian zone, which is legally designated as a protected area and prohibited from being subject to ownerhsip rights. This study aims to identify the factors behind the issuance of Land Ownership Certificate (SHM) Number 913 on riparian land along the Kanal river in Demaan Village, Jepara, as well as to analyze the implications of such issuance. Riparian zones are protected areas that cannot be privately owned under land ownership rights, as regulated by various legal frameworks, including Undang-Undang Nomor 11 Tahun 1974 tentang Pengairan, Peraturan Pemerintah Nomor 22 Tahun 1982 tentang Tata Pengaturan Air, Peraturan Menteri Pekerjaan Umum Nomor 63/PRT/1993, Peraturan Pemerintah Nomor 38 Tahun 2011 tentang Sungai, Peraturan Menteri PUPR No. 28/PRT/M/2015 and other law regulations governing riparian lands. This research uses a qualitative method with an empirical juridical approach through interviews, observation, and literature studies. The study finds two main factors contributing to the issuance of this SHM: weak transparency and verification in land administration processes, and the low level of legal awareness among the public regarding the legal status of riparian zones. These two factors reflect a lack of cross-sectoral coordination and minimal legal education at the local level. SHM Number 913 not only results in administrative flaws that could serve as grounds for certificate annulment, but also causes social injustice and ecological degradation in the surrounding area.